تأثير الأصل في تركيز عنصري الآزوت والفوسفور في المجموع الخضري لصنف التفاح Golden delicious - ديب, علي; مزهر, بيان; وسوف, فؤاد (Latakia University Journal -Biological Sciences Series, 2018)
The study was performed over the years (2014-2015) in Barshin Research Station- General Commission for Scientific Agriculture Research on the apple trees age of 15 in grafted with Golden Delicious Cultivar on two rootstocks, (strong MM109 and half strong MM106). The study focused on the effect of the rootstock on the concentration of each of the elements (N-P) in the leaves and branches of the Golden delicious Cultivar grafted on those rootstocks. The concentration of nitrogen and phosphorus in the leaves was high at the beginning of the growing season and gradually decreased with the growth season progressing. However, with the retention of leaves at the end of the growth season at a higher concentration of nitrogen and phosphorus when grow on MM109 except for the concentration of phosphorus at 2014, rootstock MM106. In the branches, we find that the concentration of nitrogen decreased significantly during the period between June and August to maintain its level later. The concentration of phosphorus was high at the beginning of the growth season and then decrease during t[1]he June period to come back and rise gradually until the end of the growth season and both studied rootstocks, In general, noticed that the accumulation of nitrogen and phosphorus in the branches during the end of the growth season is close to both. أجري البحث على مدى عامين (2014 , 2015) في محطة بحوث برشين التابعة للهيئة العامة للبحوث العلمية الزراعية على أشجار تفاح بعمر 15 عاماً من الصنف Golden delicious مطعمة على أصلين (قوي MM109 و نصف قوي MM106). ترّكزت الدراسة حول تأثير الأصل في تركيز كل من عنصري(N-P) في أوراق وفروع الصنف Golden delicious المطعم على تلك الأصول. لوحظ أن تركيز عنصري الآزوت والفوسفور في الأوراق مرتفع في بداية موسم النمو وينخفض بشكل تدريجي مع تقدم موسم النمو لكن مع احتفاظ الأوراق في نهاية موسم النمو بتركيز أعلى من الآزوت والفوسفور عند التطعيم على الأصل MM109 باستثناء تركيز عنصر الفوسفور في موسم 2014 فقد كان تراكمه أكبر لدى الأصل MM106. أما في الأفرع نجد أن تركيز الآزوت ينخفض بشكل كبير خلال الفترة الواقعة بين حزيران وآب ليحافظ على مستواه لاحقاً, أما تركيز عنصر الفوسفور فقد كان مرتفع في بداية موسم النمو ومن ثم ينخفض خلال فترة حزيران ليعود ويرتفع بشكل تدريجي حتى نهاية موسم النمو ولكلا الأصلين المدروسين, وبشكل عام نلاحظ أن تراكم عنصري الآزوت والفوسفور في الأفرع خلال نهاية موسم النمو متقارب لكلا الأصلين. * Professor, Horticulture Department, Faculty of Agriculture Engineering, Tishreen University, Lattakia , Syria. **Researcher, General Commission for Scientific Agriculture Research (GCSAR) – Syria ***High Student Degree (Doctorate), Horticulture Department , Faculty of Agriculture Engineering, Tishreen University, Lattakia ,Syria -